1999
DOI: 10.1073/pnas.96.23.13583
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana PAD4 encodes a lipase-like gene that is important for salicylic acid signaling

Abstract: The Arabidopsis PAD4 gene previously was found to be required for expression of multiple defense responses including camalexin synthesis and PR-1 gene expression in response to infection by the bacterial pathogen Pseudomonas syringae pv. maculicola. This report describes the isolation of PAD4. The predicted PAD4 protein sequence displays similarity to triacyl glycerol lipases and other esterases. The PAD4 transcript was found to accumulate after P. syringae infection or treatment with salicylic acid (SA). PAD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
520
1
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 562 publications
(549 citation statements)
references
References 45 publications
11
520
1
11
Order By: Relevance
“…The mutations in pad4-1 and dnd1-1 may be null, as they cause translation stops at aa 359 of a 542 aa protein, and aa 290 of a 720 aa protein, respectively Jirage et al, 1999). For determination of phenotypes, plants were grown in Metromix 2000 soil (Scotts-Sierra Horticultural Products, Marysville, OH, USA) in a controlled-environment chamber (22°C, 80% RH, 100 mmol m ±2 sec ±1¯u orescent illumination, 12 h light/12 h dark cycle).…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
“…The mutations in pad4-1 and dnd1-1 may be null, as they cause translation stops at aa 359 of a 542 aa protein, and aa 290 of a 720 aa protein, respectively Jirage et al, 1999). For determination of phenotypes, plants were grown in Metromix 2000 soil (Scotts-Sierra Horticultural Products, Marysville, OH, USA) in a controlled-environment chamber (22°C, 80% RH, 100 mmol m ±2 sec ±1¯u orescent illumination, 12 h light/12 h dark cycle).…”
Section: Plants and Growth Conditionsmentioning
confidence: 99%
“…In addition, EPG analysis indicated that PAD4 controls insect feeding from sieve elements (Pegadaraju et al, 2007). PAD4 is also involved in plant defense against a subset of pathogens, where it modulates the synthesis of SA and the phytoalexin, camalexin (Glazebrook et al, 1997;Zhou et al, 1998;Jirage et al, 1999). However, genetic studies have suggested that the involvement of PAD4 in plant defense against GPA is not due to its involvement in SA and camalexin metabolism .…”
Section: Pad4mentioning
confidence: 99%
“…However, genetic studies have suggested that the involvement of PAD4 in plant defense against GPA is not due to its involvement in SA and camalexin metabolism . The N-terminal half of PAD4 shares homology with α/β-fold acyl hydrolases that include lipases and esterases (Zhou et al, 1998;Jirage et al, 1999).…”
Section: Pad4mentioning
confidence: 99%
“…By having this comparison available, it is possible to suggest that the observed host response to root-knot nematodes was likely subject to some form of suppression even though the genes studied showed differential expression. The PAD4 gene of Arabidopsis, which is induced as part of the defense response to microbial pathogen infection, is another example that was confirmed to be involved in salicylate signaling by comparing its attenuated response in signaling mutants to that of wild-type plants treated directly in parallel [56]. The correct inference of host defense signaling responses can therefore only be achieved when these signals are placed in the appropriate context and contrasted to control treatments of a tissue or cell type that has relevance to the specific interaction being studied.…”
Section: Defense Marker Genes: a Question Of Contextmentioning
confidence: 99%